2021
DOI: 10.1111/jace.17673
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the fiber push‐out method to evaluate interfacial failure in SiC/BN/SiC ceramic matrix composites

Abstract: Accepted Article This article is protected by copyright. All rights reserved The investigation of several parameters during fibre push-out micromechanical tests on the interfacial shear strength (ISS) of the BN interphase in SiC f /SiC ceramic matrix composites (CMC) was undertaken to optimise experimental work. The SiC f /SiC composites-candidate materials for jet engine components-were manufactured with varying fibre types and interlayer thicknesses. Experimental parameters explored included analysing the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 43 publications
0
6
1
Order By: Relevance
“…contradicts, for example, the fibre push-out results obtained by De Meyere et al with their HNS/BN/SiC CMCs[14]. The number of tests performed is much smaller and therefore the statistical study is far from being as sound as that of De Meyer et al It should be noted, however, that with 9/ interphases our ISS values are globally higher than theirs, probably due to the initial fibre surface treatment.…”
contrasting
confidence: 60%
See 3 more Smart Citations
“…contradicts, for example, the fibre push-out results obtained by De Meyere et al with their HNS/BN/SiC CMCs[14]. The number of tests performed is much smaller and therefore the statistical study is far from being as sound as that of De Meyer et al It should be noted, however, that with 9/ interphases our ISS values are globally higher than theirs, probably due to the initial fibre surface treatment.…”
contrasting
confidence: 60%
“…The push-out tests were carried out with a nanoindenter (Micro Materials Ltd, NanoTest NTX) equipped with a flattened conical diamond tip of 5.5 µm diameter. This fulfils the optimal ratio of 1:2 for the tip:fibre diameter found by De Meyere et al to properly perform push-out tests independently on each fibre without cracking it [14]. The tests were performed under controlled force with a constant loading rate of 1 mN/s.…”
Section: Minimet™mentioning
confidence: 84%
See 2 more Smart Citations
“…Extensive experiments have been dedicated to the investigation of SiC f /SiC. De Meyere et al found that the interfacial shear strength of SiC f /SiC CMC is strongly and statistically influenced by the interfacial roughness [15]. Braun et al considered the coordination between Hi-Ni calon S fiber and SiC matrix and found that the residual thermal stress is closely related to the interfacial mismatch.…”
Section: Introductionmentioning
confidence: 99%